2011
DOI: 10.1128/jb.01130-10
|View full text |Cite
|
Sign up to set email alerts
|

Control of Heme Homeostasis inCorynebacterium glutamicumby the Two-Component System HrrSA

Abstract: The response regulator HrrA of the HrrSA two-component system (previously named CgtSR11) was recently found to be repressed by the global iron-dependent regulator DtxR in Corynebacterium glutamicum. Here, we provide evidence that HrrA mediates heme-dependent gene regulation in this nonpathogenic soil bacterium. Growth experiments and DNA microarray analysis revealed that C. glutamicum is able to use hemin as an alternative iron source and emphasize the involvement of the putative hemin ABC transporter HmuTUV a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 51 publications
3
81
0
Order By: Relevance
“…1.5-fold) in the DchrSA mutant. Together with the observed derepression of chrSA in a DhrrA mutant (Frunzke et al, 2011) these data hint at a cross-regulation of both systems at the level of transcription. Further genes exhibiting an altered mRNA level include a regulator of unknown function (cg3303) and the redox-sensing regulator qorR, whose DNA-binding activity was reported to be affected by oxidants (Ehira et al, 2009).…”
Section: The Hrtba Transporter Confers Resistance Towards Haem Toxicitymentioning
confidence: 74%
See 4 more Smart Citations
“…1.5-fold) in the DchrSA mutant. Together with the observed derepression of chrSA in a DhrrA mutant (Frunzke et al, 2011) these data hint at a cross-regulation of both systems at the level of transcription. Further genes exhibiting an altered mRNA level include a regulator of unknown function (cg3303) and the redox-sensing regulator qorR, whose DNA-binding activity was reported to be affected by oxidants (Ehira et al, 2009).…”
Section: The Hrtba Transporter Confers Resistance Towards Haem Toxicitymentioning
confidence: 74%
“…The TCS ChrSA (previously CgtSR8): sequence similarities and genomic organization In a previous study the TCS HrrSA was reported to play a central role in the control of haem homeostasis in C. glutamicum (Frunzke et al, 2011). In vitro DNA binding studies with purified HrrA protein provided evidence that the response regulator HrrA binds to the upstream promoter region of an operon encoding another TCS, chrSA (cg2201-cg2200) (Kocan et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations